2011
DOI: 10.1002/ana.22381
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in children and adolescents with stroke, self‐reports, and parent/proxies reports: Cross‐sectional investigation

Abstract: Pediatric stroke survivors compared with healthy controls are strongly affected regarding their overall well-being and older children/adolescents regarding their well-being with peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 35 publications
7
67
1
3
Order By: Relevance
“…Studies found that younger age at stroke onset was significantly associated with poorer QoL in the domains of physical functioning and neurological outcome [13], long-term clinical outcomes and independence in daily activities [44,46], adaptive functioning skills [47], and overall outcome [16]. In contrast, younger age at stroke was associated with better overall well-being and quality of life [20] and better self-rated self-esteem and social participation [21] in other studies. Older age at stroke was associated with more behavioural difficulties in another study [29].…”
Section: Factors Associated With Psychosocial Outcomementioning
confidence: 97%
See 4 more Smart Citations
“…Studies found that younger age at stroke onset was significantly associated with poorer QoL in the domains of physical functioning and neurological outcome [13], long-term clinical outcomes and independence in daily activities [44,46], adaptive functioning skills [47], and overall outcome [16]. In contrast, younger age at stroke was associated with better overall well-being and quality of life [20] and better self-rated self-esteem and social participation [21] in other studies. Older age at stroke was associated with more behavioural difficulties in another study [29].…”
Section: Factors Associated With Psychosocial Outcomementioning
confidence: 97%
“…Twenty-six studies did not recruit a control group but compared scores to published normative population data. Of the remaining ten that did recruit control participants, these included typically developing children as controls [20,8,21]; children with other non-neurological health conditions, such as orthopaedic and chronic asthma controls [22,23,24,25,26,21,8]; and some children with other neurodevelopmental conditions but without stroke, such as sickle cell disease controls [27] or malformations of cortical development [28]. The participant sample sizes in the studies ranged from fourteen children [28] to 163 children [2].…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
See 3 more Smart Citations